Coupling of UHPLC with fast fraction collection–microplate scintillation counting and MS for radiolabeled metabolite profiling. (June 2012) - Tong, Wei; Chowdhury, Swapan; Wrona, Mark; Bateman, Kevin
Background: To further expand the use of fraction collection (FC)–microplate scintillation counting (MSC) in detecting trace amount of radioactivity in absorption, distribution, metabolism and excretion (ADME) studies and improve the resolution of UHPLC–FC–MSC, we report the coupling of UHPLC with MS and faster FC (1.2 s/fraction) followed by MSC using 384-deep-well LumaPlate™ (PerkinElmer, MA, USA) for profiling of radiolabeled metabolites in plasma, urine, bile and feces.Results: Collection of 1.2 s/well clearly improved the resolution of the reconstructed radiochromatograms and, at the same time, provided sufficient detection sensitivity that allowed for more accurate integration of peaks, which is required for radiolabeled ADME studies. The introduction of a reversed gradient as a make-up solvent mixture ensured more uniform drops collected in each well, with resolution maintained throughout the UHPLC run. Less sample injection and more frequent FC resulted in less quenching by matrix and accurate integration of peak.Conclusion: UHPLC–FC–MSC–MS is suitable for metabolite profiling in ADME studies and offers higher resolution, higher sensitivity, shorter LC running time, reduced matrix effect and more environmentally friendly experiments compared with conventional online flow scintillation analysis.